When does limited commitment matter in a production economy? - CHOI, Kyoung Jin (Institutional Knowledge at Singapore Management University, 2018)
We investigate the conditions under which the ﬁrst-best allocation without commitment is sustainable in a production economy. While it is widely known in the literature that allowing capital accumulation creates a distortion, we ﬁnd that it can help to sustain the ﬁrst-best allocation. We also ﬁnd that for a certain set of endowment economiesin which the eﬃcient allocation is not sustainable, the eﬃcient allocation becomes sustainable once we introduce a production technology with very small returns to scale orany returns to scale higher than that of the minimum value. In some cases, gains fromeﬃcient resource allocation between agents can be so large that they can compensate forthe increase in the outside option that arises when capital moves from the less-productiveto the more-productive agent.